Toxoplasma gondii modulates the host cell cycle, chromosome segregation, and cytokinesis irrespective of cell type or species origin - Lisbeth Rojas-Baron; Kira Senk; Carlos Hermosilla; Anja Taubert; Zahady D. Velásquez (Parasites & Vectors, 2024)
Abstract﻿ Background Toxoplasma gondii is an apicomplexan intracellular obligate parasite and the etiological agent of toxoplasmosis in humans, domestic animals and wildlife, causing miscarriages and negatively impacting offspring. During its intracellular development, it relies on nutrients from the host cell, controlling several pathways and the cytoskeleton. T. gondii has been proven to control the host cell cycle, mitosis and cytokinesis, depending on the time of infection and the origin of the host cell. However, no data from parallel infection studies have been collected. Given that T. gondii can infect virtually any nucleated cell, including those of humans and animals, understanding the mechanism by which it infects or develops inside the host cell is essential for disease prevention. Therefore, we aimed here to reveal whether this modulation is dependent on a specific cell type or host cell species. Methods We used only primary cells from humans and bovines at a maximum of four passages to ensure that all cells were counted with appropriate cell cycle checkpoint control. The cell cycle progression was analysed using fluorescence-activated cell sorting (FACS)-based DNA quantification, and its regulation was followed by the quantification of cyclin B1 (mitosis checkpoint protein). The results demonstrated that all studied host cells except bovine colonic epithelial cells (BCEC) were arrested in the S-phase, and none of them were affected in cyclin B1 expression. Additionally, we used an immunofluorescence assay to track mitosis and cytokinesis in uninfected and T. gondii-infected cells. Results The results demonstrated that all studied host cell except bovine colonic epithelial cells (BCEC) were arrested in the S-phase, and none of them were affected in cyclin B1 expression. Our findings showed that the analysed cells developed chromosome segregation problems and failed to complete cytokinesis. Also, the number of centrosomes per mitotic pole was increased after infection in all cell types. Therefore, our data suggest that T. gondii modulates the host cell cycle, chromosome segregation and cytokinesis during infection or development regardless of the host cell origin or type. Graphical Abstract